2022
DOI: 10.1177/14687941221087869
|View full text |Cite
|
Sign up to set email alerts
|

“Nothing about us without us”: Tending to emancipatory ideologies and transformative goals in participatory action research partnerships

Abstract: In this paper, a collaborative group of university researchers and a community organizer who participated in a 2-year participatory action research (PAR) partnership reflect upon their inquiry process and analyze its effects. Authors examine the benefits, challenges, and potential of using PAR to advance educational justice and transformative goals amidst austere neoliberal education reforms, such as public school closure and state sanctioned privatization. Authors consider ways PAR can reflect emancipatory id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Involving community members and other stakeholders in ongoing public health research and policy development is critical, as demonstrated by the engagement of participants in the current project. Other recent papers support the notion that involvement of multiple stakeholders, especially community members, is critical to improving public health strategies and policy initiatives, while also reducing community inequalities [ 27 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Involving community members and other stakeholders in ongoing public health research and policy development is critical, as demonstrated by the engagement of participants in the current project. Other recent papers support the notion that involvement of multiple stakeholders, especially community members, is critical to improving public health strategies and policy initiatives, while also reducing community inequalities [ 27 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 98%
“…They are frequently ignored or passed by in efforts to scope out or plan public health interventions. Across the state, one of the responses that was commonly heard was “don’t do anything about me without me” or the historically more common “nothing about us without us” [ 27 ]. People are eager to have a voice in decisions that would impact their health and environment, and to learn more about how the two are connected.…”
Section: Discussionmentioning
confidence: 99%
“…Embarking on the journey of qualitative research demands a continuous commitment to vulnerability, honesty, and critical self-reflection (Herr & Anderson, 2014;Wilson et al, 2022).…”
Section: Positionalitymentioning
confidence: 99%
“…These roles included, but were not limited to, vice principals, instructional coaches, deans, and program directors. In action research, the partnerships that exist between the researcher and stakeholders are critical to building trust and enabling social change that disrupts oppression in urban communities (Herr & Anderson, 2014;Wilson et al, 2022). The collaboration with internal and external stakeholders helped shape the…”
Section: Participants/collaborators/stakeholders Experiencementioning
confidence: 99%
See 1 more Smart Citation